If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10 + -1x = 16 Solving -10 + -1x = 16 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + -1x = 16 + 10 Combine like terms: -10 + 10 = 0 0 + -1x = 16 + 10 -1x = 16 + 10 Combine like terms: 16 + 10 = 26 -1x = 26 Divide each side by '-1'. x = -26 Simplifying x = -26
| 4n+2.2=9.4 | | 4s^2-16st+16t^2= | | (16x-4)+(2x+13)=90 | | 4v^2+12v+9= | | -.2u-.5=.33 | | 3z=16-22 | | 3x+17.2+8= | | -1/5u-1/2=1/3 | | 1.5=1.2x-5.7 | | -3rd+10=15r-8 | | 9t-4t-12t-15t= | | 3x-1=-167 | | 90-(16x-4)=90-(2x+13) | | 0.25n^2-0.3n+0.09= | | 24=3+2x | | a-3=1+1+4a-2 | | 3(3y+5)=79 | | 90-16x-4=90-2x+13 | | 12(v+2)-4v=2(4v+2)-12 | | 2x+7=105 | | 8x+15=4x+55 | | -7a-4a=11 | | v^2w^2-1= | | 40-[4+7y-2(y+5)]=-3(3y-7)-[5(y-1)-3y+10] | | -1.4(12+h)=7 | | d=hs | | x/6=3x/5-13 | | 16x-13=5(3x+4)-7 | | 2y=2y^2+4 | | -5w+18w= | | 9a-(11+3a)+5= | | -12n+3=-11n-10 |